The Influence Of Human Resource Management Practices On Organizational Effectiveness Mediated By Work Involvement And Performance Of Police Personnel In Southeast Sulawesi Regional Police - Sabar, Abdul; Madjid, Rahmat; Zaid, Sudirman; Mahrani, Sri Wiyati (Journal of Neonatal Surgery, 2025)
This study aims to analyze the effect of human resource management practices (HRMP) on organizational effectiveness at the Southeast Sulawesi Regional Police, mediated by work engagement and police personnel performance. This research also analyzes the direct and indirect effects of HRMP, work engagement, and personnel performance on organizational effectiveness at the Southeast Sulawesi Regional Police. The method used in this study is quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships between these variables. Data was collected through a questionnaire distributed to personnel at the Southeast Sulawesi Regional Police, with 349 respondents. The results of the study show that good human resource management practices, such as relevant training, proper motivation, and development opportunities for personnel, have a positive and significant impact on organizational effectiveness. Good HRMP also enhances work engagement among personnel, which in turn improves their performance. Optimal personnel performance contributes to organizational effectiveness, indicating that individual performance is a key element in achieving organizational goals. Furthermore, work engagement was found to strengthen the relationship between HRMP and organizational effectiveness, with personnel performance acting as a mediator between work engagement and organizational effectiveness. This study provides evidence that effective HRMP, including training and performance rewards, can improve personnel engagement and performance, which in turn enhances organizational effectiveness. These findings suggest that improving HRM management can serve as a main driver for increasing organizational effectiveness at the Southeast Sulawesi Regional Police. Therefore, good HRMP is essential for achieving better and more efficient organizational goals.